Gas-phase fragmentation of deprotonated tryptophan and its clusters [Trpn-H]- induced by different activation methods - Feketeová, Linda; Khairallah, George N.; O'Hair, Richard A. J.; Nielsen, Steen Brøndsted (Rapid communications in mass spectrometry, 2015)
Rationale Non‐covalent amino acid clusters are the subject of intense research in diverse areas including peptide bond formation studies or the determination of proton affinities or methylating abilities of amino acids. However, most of the research has focused on positive ions and little is known about anionic clusters. Methods Fragmentation reactions of deprotonated tryptophan (Trp), [Trp−H]− and Trp singly deprotonated non‐covalently bound clusters [Trpn−H]−, n = 2, 3, 4, were investigated using low‐energy collision‐induced dissociation (CID) with He atoms, high‐energy CID with Na atoms, and electron‐induced dissociation (EID) with 20–35 eV electrons. Fragmentation of the monomeric Trp anion, where all labile hydrogens were exchanged for deuterium [d4‐Trp−D]−, was investigated using low‐energy CID and EID, in order to shed light on the dissociation mechanisms. Results The main fragmentation channel for Trp cluster anions, [Trpn−H]−, n >1, is the loss of the neutral monomer. The fragmentation of the deprotonated Trp monomer induced by electrons resembles the fragmentation induced by high‐energy collisions through electronic excitation of the parent. However, the excitation must precede in a different way, shown through only monomer loss from larger clusters, n >1, in case of EID, but intracluster chemistry in the case of high‐energy CID. Conclusions The anion of the indole ring C8H6N− has been identified in the product ion spectra of [Trpn−H]− using all activation methods, thus providing a diagnostic marker ion. No evidence was found for formation of peptide bonds as a route to prebiotic peptides in the fragmentation reactions of these singly deprotonated Trp cluster ions. Copyright © 2015 John Wiley & Sons, Ltd.